Competitiveness of the European economy - Michael Landesmann; Sandra Leitner; Robert Stehrer (European Investment Bank (EIB), 2015)
This paper examines developments in market share, export structure and revealed comparative advantage within the EU and in comparison with other regions of the world. It pays special attention to shifts in specialisation and export structure with regard to manufacturing and services, lower and higher technology industries and business services. Data are taken from the World Input-Output Database (WIOD), which provides information on international production process linkages and allows calculation of measures of "trade in value added".
Keywords: 330